Factors influencing the behavioral intention to use Cryptocurrency among Saudi Arabian public university students: Moderating role of financial literacy - Ali S. A. Alomari; Nasuha L. Abdullah (Cogent Business & Management)
This study aims to investigate the factors that can predict the behavioral intention of students at public universities in Saudi Arabia to use Cryptocurrency. The UTAUT model was enhanced with the incorporation of security and awareness to develop the theoretical model for this investigation. The paper investigates the impact of performance expectancy, effort expectancy, facilitating condition, social influence, security, and awareness on the behavioral intention to use Cryptocurrency. The moderating role of financial literacy was also investigated on the associations between the proposed adoption factors and the behavioral intention to use Cryptocurrency. SmartPLS 3.2.8 software was used to analyse 344 responses collected via an online survey. The Findings showed that performance expectancy, effort expectancy, social influence, security, and awareness positively impact on behavioral intention to use Cryptocurrency. Moreover, financial literacy moderates the associations between performance expectancy, security, social influence, and behavioral intention. The findings offer valuable insights to Cryptocurrency users, Cryptocurrency developers, and the government of the KSA.